Dearth of influenza among older adults admitted with respiratory symptoms in Malaysia during the coronavirus disease 2019 pandemic in 2021 - Tan, Maw Pin; Leong, Chee Loon; Pang, Yong Kek; Razali, Rizah Mazzuin; Ismail, Ahmad Izuanuddin; Sam, I-Ching; Abdul Rani, Rosilawati; Chong, Jennifer; Mohd Zim, Mohd Arif; Musa, Aisya Natasya; Leong, Jia Hui; Idris, Salmah; et al. (Frontiers in Medicine, 2022)
Introduction Influenza is a common respiratory virus which leads to over 400,000 annual deaths globally. Mortality from influenza is highest among those aged 75 years and over living in Africa and Southeast Asia. Objective To determine the burden of influenza among older adults presenting to public hospitals with severe acute respiratory infection (SARI) during the coronavirus disease 2019 (COVID-19) pandemic. Methods This multi-center, prospective, observational study recruited individuals aged 65 years and over who presented to four Malaysian hospitals with SARI from 1 January to 31 December 2021. Those with prior confirmed severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection were excluded. SARS-CoV-2 was detected through real-time polymerase chain reaction (PCR) with routine diagnostic kits. Influenza A, influenza B and respiratory syncytial (RSV) viruses were detected with Xpress Flu/RSV kits using the GeneXpert rapid real-time PCR system (Cepheid, USA). Results Samples were obtained from 512 participants, comprising 296 (57.8%) men and 216 (42.2%) women, with a mean age (SD) of 74.0 (7.1) years. Inpatient death occurred in 48 (9.6%) individuals. Significant differences existed in age, ethnicity, and comorbidities across study sites. One (0.2%) case of influenza A, two (0.4%) cases of RSV and 63 (12.5%) cases of SARS-CoV-2 infection were detected over the one-year period. Cases of COVID-19 mirrored national trends derived from open source data, while the dearth of influenza cases mirrored national and global Flunet figures. Conclusion Our observational study conducted during the COVID-19 pandemic detected only one case of influenza, alongside a high SARS-CoV-2 positivity rate. The poor uptake of influenza vaccination nationally, worsened by the recent pandemic restrictions, could lead to waning immunity from the absence of seasonal exposure. Potentially deadly outbreaks may then occur when lockdown and infection control measures are eventually removed.